HEALTH STATUS OF DELHIITES DUE TO HUGE POLLUTION INDEX - A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Delhi has consistently ranked among the world's most polluted cities (IQ Air 2021). Just in 2019, air pollution was responsible for almost 17,000 premature deaths and a loss of economic activity equal to 1,207 million US dollars in the nation's capital. The year 2020 was an outlier with relation to the quality of the air. The precautions taken in response to the pandemic-induced lockdown afforded a little reprieve from the consistently bad air quality. Over the course of the past decade, the Government of Delhi has implemented a number of different programmes in an effort to reduce the amount of air pollution that exists within the city. Nevertheless, additional steps are required in order to bring the levels of air pollution further down. The measures that are now in place require both reinforcement and amplification so that they can be used on a greater scale. In addition to the response from the authorities, the participation of the community is essential if there is to be any discernible influence made on the decrease of pollution. There is a pressing need to promote the use of public transportation. The utilisation of the Metro train system may be improved. It is important that people be made more aware of the need to turn off their automobiles when they are waiting in traffic. This study is an attempt to showcase the level of pollution in Delhi & how Delhiites are getting affected due to this HPI & what’s the impact on them.